Efficacy of acupuncture for chronic knee pain: protocol for a randomised controlled trial using a Zelen design - Hinman Rana S; McCrory Paul; Pirotta Marie; Relf Ian; Crossley Kay M; Reddy Prasuna; Forbes Andrew; Harris Anthony; Metcalf Ben R; Kyriakides Mary; Novy Kitty; Bennell Kim L (BMC, 2012)
Abstract Background Chronic knee pain is a common and disabling condition in people over 50 years of age, with knee joint osteoarthritis being a major cause. Acupuncture is a popular form of complementary and alternative medicine for treating pain and dysfunction associated with musculoskeletal conditions. This pragmatic Zelen-design randomised controlled trial is investigating the efficacy and cost-effectiveness of needle and laser acupuncture, administered by medical practitioners, in people with chronic knee pain. Methods/Design Two hundred and eighty two people aged over 50 years with chronic knee pain have been recruited from metropolitan Melbourne and regional Victoria, Australia. Participants originally consented to participate in a longitudinal natural history study but were then covertly randomised into one of four treatment groups. One group continued as originally consented (ie natural history group) and received no acupuncture treatment. The other three were treatment groups: i) laser acupuncture, ii) sham laser or, iii) needle acupuncture. Acupuncture treatments used a combined Western and Traditional Chinese Medicine style, were delivered by general practitioners and comprised 8-12 visits over 12 weeks. Follow-up is currently ongoing. The primary outcomes are pain measured by an 11-point numeric rating scale (NRS) and self-reported physical function measured by the Western Ontario and McMaster (WOMAC) Universities Osteoarthritis Index subscale at the completion of treatment at 12 weeks. Secondary outcomes include quality of life, global rating of change scores and additional measures of pain (other NRS and WOMAC subscale) and physical function (NRS). Additional parameters include a range of psychosocial measures in order to evaluate potential relationships with acupuncture treatment outcomes. Relative cost-effectiveness will be determined from health service usage and outcome data. Follow-up assessments will also occur at 12 months. Discussion The findings from this study will help determine whether laser and/or needle acupuncture is efficacious, and cost-effective, in the management of chronic knee pain in older people. Trial registration Australian New Zealand Clinical Trials Registry reference: ACTRN12609001001280